FLUID RESUSCITATION IN CARDIOGENIC SHOCK: AN ASSESSMENT OF RESPONSIVENESS AND OUTCOME - Memon, Aziz-ur Rehman; Ansari, Muhammad Imran; Shaikh, Shahbaz Ali; Abubaker, Jawed; Karim, Musa; Salahuddin, Nawal (Journal of Ayub Medical College Abbottabad, 2021)
Background: Fluid replacement for resuscitation in cardiogenic shock (CS) patients remains a point of debate in clinical practice. The purpose of the study was to assess the frequency of fluid responsiveness and outcomes of patients with cardiogenic shock receiving fluid resuscitation at the critical care unit (ICU) of a tertiary care cardiac center. Methods: In this descriptive case series, in which all mechanically ventilated CS patients were evaluated who were assessed for fluid responsiveness by a fluid challenge. It was conducted at the critical care unit of a tertiary care cardiac center in Karachi, Pakistan, from January 2020 to June 2020, by including 41 consecutive patients. Fluid challenge was given as either a 250 ml crystallized bolus or a passive leg raise (PLR) manoeuvre. An increase in the velocity time integral (ˆ†VTI) of ‰¥ 10% was considered fluid responsiveness. Results: A total of 41 patients were evaluated: 25 (61%) were males, and the mean age was 61.9±17.0 years, and 36.6% (15) of the patients presented with non-ST elevation myocardial infarction (NSTEMI), followed by anterior wall ST elevation myocardial infarction (31.7% (13)). Fluid responsiveness was observed in 48.8% (20/41). Mean VTI change after the fluid challenge was 1.07±0.86. Survival rate was 33.3% (7/21) in fluid responders vs. 50.0% (10/20) in non-fluid responders; p=0.279. Conclusion: Almost half of patients presenting with CS from acute coronary syndrome are responsive to fluids. These findings support the routine evaluation by fluid challenge in these patients. Fluid challenge can be by either PLR or fluid bolus.